436 Remote Surgical Education for Medical Students at UK Universities in the Time of COVID-19. (4th May 2021) - Zaver, V; Ahari, D; Jayawardena, P; Sayed, Md A
Abstract: Background: The novel coronavirus pandemic caused the cancellation of lectures and clinical placement-based education for medical students across the UK. With phased resumption of University teaching, remote delivery via online platforms has seen increased implementation to prevent overcrowding and comply with social distancing measures. This study explores the efficacy of a nationally delivered online surgical education programme to facilitate undergraduate surgical education. Methods: An undergraduate surgical society in collaboration with two Core Surgical Trainees designed and organised an online surgical teaching programme. The syllabus was constructed in accordance with the Royal College of Surgeons England's (RCSEng) National Undergraduate Curriculum in Surgery. Remote delivery was facilitated by Zoom (Zoom Video Communications, Inc.). Multiple-choice questionnaires were used to evaluate knowledge during the sessions and Likert scales were utilised to assess subjective improvement of knowledge. Results: The average attendance for the lectures was 100. The average increase in correct answers between pre- and post-lecture multiple choice questions was +55.87% (+72.4, +18.6, +76.6). Likert scale analysis demonstrated 100% improvement of knowledge. Conclusions: This study demonstrates a positive outcome to remote, extra-curricular surgical education in the time of COVID-19. The methodology outlined herein has the potential to be adopted by other Universities to facilitate undergraduate surgical education.